Examining the Impact of Omnichannel Integration on Satisfaction, Trust and Customer Loyalty: The Moderating Role of Prior Online Experience - Gowrie, Nerisha; Shetty, Fiza; Chopra , Komal; Ligaraba, Neo (International Review of Management and Marketing, 2026)
Omnichannel integration is transforming grocery retail, redefining customer interactions, experiences, and relationship management across digital and physical channels. This study investigates how omnichannel integration in grocery retail—including promotion, product and price, transaction information, order fulfilment, and customer service—influences satisfaction, trust, and customer loyalty in South Africa, while also examining the moderating role of prior online experience. Survey data from 185 consumers who shop both online and in-store were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that integrated product and price is the strongest predictor of satisfaction, which subsequently influences trust and customer loyalty. Contrary to expectations, prior online experience did not significantly moderate these relationships, suggesting that rapid digital adoption and intuitive omnichannel design have largely closed the gap between novice and experienced shoppers. The study contributes to omnichannel and relationship marketing literature in an emerging market context and demonstrates that cohesive, user-friendly omnichannel strategies enhance satisfaction, trust, and customer loyalty, offering actionable guidance for grocery retailers seeking to strengthen customer relationships.